A Digital Data Acquisition System for High Subsonic Speed Wind Tunnels - El-Ibrahim, Dr. Salah. J. S. (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
The need to reduce time and cost of running high speed (transonic & supersonic) wind tunnels and to obtain reliable experimental data is very essential to the academic and industrial worlds of aviation. Data acquisitioning technology together with the advents in computer programming made the prospects of upgrading old technology wind tunnels (those manually driven and using mercury or water manometers) a reality. Simple hardware and software are available and are cheap and very effective and can be easily installed for the purposes stated. The present paper describes a data acquisition system, suggested and installed, by the author for use on the supersonic wind tunnel at the university of Hertfordshire/UK. The tunnel layout and the acquisition system are described together with some of the validation experimental runs. The experiments were carried out originally as part of the author’s PhD research work investigating the effects of aerofoil surface irregularities at high subsonic speeds using the viscous Garabedian & Korn (VGK) method [1].